Fetomaternal Outcome of Emergency Caesarean Section in a Tertiary Level Hospital (Ibrahim Cardiac Medical Journal, 2019)
Background & objective: Acute threat to the pregnant mother or their foetus may arise during the process of labor or any time after 28 weeks of gestation, when emergency caesarean section (CS) is indicated. But emergency CS is not completely safe to the mother or their foetus. The present study was undertaken to observe the foetomaternal outcome of emergency caesarean section.Methods: This prospective observational study was conducted between January to June, 2010 in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka. All pregnant women undergoing emergency CS admitted at the the above-mentioned Hospital were the study population. The indications for emergency CS were obstructed labour, fetal distress, prolonged labour, cord prolapse, antepartum hemorrhage, antepartum eclampsia with unfavorable cervix labor with malpresentation, history of previous one caesarean section with impending scar rapture, chorioamnionitis, failed forceps/ventous etc. A total of 672 pregnant women based on predefined eligibility criteria were consecutively included in the study and fetomaternal outcome of emergency CS was evaluated.Result: Age distribution of the patients shows that over 30% were 25-29 years, 26.5% 30-34 years, 23.3% 20-24 years old. About 10% were < 20 years and another 10% were 35 or > 35 years old. Over 20% of the mothers were short-statured (< 140 cm), 60% were nullipara, 16.5% primipara and the rest were multipara. The indications for emergency caesarean sections were previous caesarean section with complications (23.7%) followed by foetal distress (16.2%), antepartum hemorrhage (APH) (8.6), eclampsia (7.8%), obstructed labor (7.4%), severe preeclampsia, breech, prolonged labor, cephalopelvic disproportion, PROM etc. About 25% of the women were preterm, 57% were term and 18% were post-term. A total of 230(34.2%) patients developed complications following caesarean section. Wound infection (14.3%) was the most common complication followed by wound dehiscence, puerperal pyrexia, anaemia, primary PPH, UTI, anesthesic hazarads and vesico-vaginal fistula. Sixteen (2.4%) mother died of complications. Most common causes of death were postpartum haemorrhage (12%), severe preeclampsia & eclampsia (7.1%), puerperal sepsis with septicemia (3.6%) and cardiac arrest. About 94% of fetuses were born alive, 5% were stillborn and 1% born with congenital anomalies. Early perinatal death occurred in 10% cases who were born alive, 5.2% had neonatal jaundice and 3.3% developed septicemia. Finally, 559 (83.1%) were discharged healthy. Of the total 113 perinatal deaths, 68 were early perinatal death.Conclusion: The findings of the present study suggest that increased perinatal mortality was due to severe birth asphyxia following obstructed labour, placenta praevia, PROM with chorioamnionitis and eclampsia. Proper antenatal care, screening of high-risk pregnancy, timely hospital admission, neonatal resuscitation and establishment of specialized neonatal care unit can significantly reduce perinatal morbidity and mortalityIbrahim Card Med J 2017; 7 (1&2): 92-98